Analisis Faktor yang Berhubungan dengan Kepercayaan Diri Akibat Timbulnya Acne Vulgaris pada Remaja Berdasarkan Teori Adaptasi Roy di SMA 17 Agustus 1945 Surabaya - Tri Agustiningsih; Retnayu Pradanie; Ika Nur Pratiwi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
ABSTRACT Abstract: 85% adolescent in 15-18 years old suffers from acne vulgaris (Ayudianti & Indramaya 2014). Acne vulgaris can cause inflammation of the face, that can cause low self-confident’s problem too. The pupose of this study is to investigate correlation between physical aspect (phsycal appereance), social aspect (parent support), mental aspect (self perspective), and people knowledge about acne vulgaries. The purpose of this study is to investigate correlation with cross sectional approach. Data were collected using total sampling method and gain 156 respondents of first year and second year in SMA 17 Agustus 1945. Respondents were 156 people and recruited by total sampling method. The independent variable of this study is physical aspect (phsycal appereance), social aspect (parent support), mental aspect (self perspective), and people knowledge. The dependent variable of this study is self-confidance. Data were collected using quissionaire and analyzed using spearman’s rho with significance level α<0,05. This study with significance level 0,000 showed correlation between physical aspect (physical appereansce) is 0,322, social aspect (parents support) is 0,778, mental aspect (self perspective) is 0,304, and knowledge is 0,377 towards self-confidance level in adolescent as result of acne vulgaris. There is significant correlation between physical aspect (phsycal appearance), social aspect (parents support), mental aspect (self perspective), and knowledge with self-esteem level as consequence of acne vulgaris. The next researcher is expected to give intervention in respondents of this study. It is also recommended at UKS nurses develop interventions suchKeywords : acne vulgaris, phsycal appereance, parents support, self perspective, knowledge, and self-confidance, adolescent.